Skewed distributions of lifetime reproductive success: beyond mean and variance - Shripad Tuljapurkar; Wenyun Zuo; Tim Coulson; Carol Horvitz; Jean‐Michel Gaillard (Ecology Letters, 2020)
Lifetime reproductive performance is quantified here by the LRS (lifetime reproductive success), the random number of offspring an individual produces over its lifetime. Many field studies find that distributions of LRS among individuals are non‐normal, zero‐inflated and highly skewed. These results beg the question, what is the distribution of LRS predicted by demographic models when the only source of randomness is demographic stochasticity? Here we present the first exact analysis of the probability distribution of LRS for species described by age + stage models; our analysis starts with estimated vital rates. We illustrate with three examples: the Hadza, human hunter‐foragers (age‐only), the evergreen tree Tsuga canadensis (stage‐only) and Roe deer, Capreolus capreolus (age + stage). For each we obtain the exact distribution of LRS, but also calculate and discuss the first three moments. Our results point to important questions about how such LRS distributions affect natural selection, and life history evolution.